Principles of Circumstantial Evidence in Handling Criminal Cases - Wibowo, Hari; Arganova A, Dicky (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
There are no provisions related to circumstantial evidence in the handling of criminal cases. However, there are several judges' decisions that use circumstantial evidence in criminal cases, so that the decision does not reach the highest degree of justice and legal certainty in a decision, because it is not based on the minimum requirement of two pieces of evidence that must be met in terms of proof to impose a criminal sentence. As for the formulation of the problem in this study are: (1) the philosophy of circumstantial evidence from the perspective of criminal procedural law. (2)ius constituendum application of circumstantial evidence in the process of proving criminal cases. This research is a normative research, which is a technique or procedure of review based on several legal principles, legal principles, and legal principles relating to the substance of legislation that is general and specific in nature in order to answer the legal issues raised.Keywords: Circumstantial Evidence, Criminal Cases